2022
DOI: 10.1016/j.clet.2022.100440
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of COVID-19 prevention and protection measures in hospitals

Abstract: This paper aims to develop an assessment framework for the Covid-19 prevention and protection measures in hospitals. The conceptual model is developed by using fifty-four attributes, fifteen criteria, and three enablers. The multi-grade fuzzy approach is used to develop the assessment framework, and Importance Performance Analysis (IPA) identifies the weaker attributes in the case organization. The case hospital's preventive and safety measures assessment level is 8.05, which is ‘very highly focused on protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…As a result, they conclude the study by identifying various current and future research directions. On the other hand, a framework for evaluating COVID-19 prevention and protection strategies in hospitals was discussed in [ 18 ]. COVID-19 recommendations for preventative and protective measures, tight procedures, frequent audits, staff education and training, and active monitoring should emphasise the case hospital management.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, they conclude the study by identifying various current and future research directions. On the other hand, a framework for evaluating COVID-19 prevention and protection strategies in hospitals was discussed in [ 18 ]. COVID-19 recommendations for preventative and protective measures, tight procedures, frequent audits, staff education and training, and active monitoring should emphasise the case hospital management.…”
Section: Related Workmentioning
confidence: 99%
“…e amount of energy consumed in data transmission increases the distance between the transmission and reception nodes. When selecting CH, the remaining energy in the sensors, as well as their maximum and minimum distances from the BS, are taken into consideration omas and Suresh [18] Hospital management Every piece of data is accessible by approved login from anywhere in the globe. is form of communication has become considerably less expensive.…”
Section: Cluster-head Selection Using Fuzzy Logicmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19) is still causing extensive damage worldwide despite the development of treatment methods and vaccines [ 1 ]. As COVID-19 is highly contagious, has a long incubation period, and is airborne, and considering the burden of in-hospital COVID-19 outbreaks, hospitals have established numerous prevention strategies, including providing caregivers with personal protective equipment (PPE), limiting visiting hours for general wards and intensive care units (ICUs), and frequent testing of patients and their caregivers for COVID-19 [ 2 , 3 , 4 ]. Nevertheless, nosocomial COVID-19 outbreaks have been reported continuously during the pandemic [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study suggested that the ISM method could benefit these contexts by developing approaches for integrating technology and capturing and developing knowledge (Shankar et al, 2003). Furthermore, the ISM approach is increasingly being used in chemical laboratories to support the instruction of students in knowledge-based settings (Shankar et al, 2003).ISM is used in the service sector, which includes the healthcare industry, start-ups, and higher education (Thomas et al, 2022;Vaishnavi et al, 2019;Sreenivasan et al, 2022a;Menon et al, 2020) to discover enablers for effective management. This model has generated crucial inputs for government officials to improve the policies for enhancing these service sectors.…”
Section: Introductionmentioning
confidence: 99%